Stereotactic ablative radiotherapy in T1-2N0M0 small cell lung cancer: A systematic review and meta-analysis. (October 2021) - Safavi, Amir H.; Mak, David Y.; Boldt, R. Gabriel; Chen, Hanbo; Louie, Alexander V.
Highlights: This meta-analysis reviews oncologic and toxicity outcomes of SABR for T1-2N0M0 SCLC. High local control rates were observed at 3 years of follow-up. Toxicity of SABR was uncommon and mostly of mild and moderate severity. Nodal and distant recurrences highlight need for chemotherapy and complete staging. Prospective data are needed to further clarify the role of SABR for these patients. Abstract: Objectives: Stereotactic ablative radiotherapy (SABR) is used to treat inoperable early-stage, node-negative small cell lung cancer (SCLC). We performed a systematic review and meta-analysis of the literature on SABR for T1-2N0M0 SCLC to summarize outcomes including local control (LC), overall survival (OS), recurrence rates, and toxicity. Materials and methods: This study was conducted in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) and MOOSE (Meta-analysis of Observational Studies in Epidemiology) guidelines. A systematic review of PubMed and EMBASE (inception to April 2021) was conducted. Two authors independently reviewed articles for inclusion and extracted study-level data. Random-effects meta-analysis was conducted using R (version 3.6.2) at a significance threshold of 0.05. Results: Eleven studies were identified in the systematic review and seven (399 patients) were selected for meta-analysis. Inoperability was noted as the indication for SABR in 94% (75–100%) of patients. Median follow-up and tumor size were 19.5 months (11.9–32) and 24 mm (19–29), respectively. Chemotherapy and PCI use rates were 44.1% (95% confidence interval [CI], 27.0–61.9%) and 13.8% (95% CI, 0.4–41.2%), respectively. Local control was 97.3% (95% CI, 92.3–99.8%) at 1 year and 95.7% (95% CI, 74.2–100.0%) at 2 years. Overall survival was 86.3% (95% CI, 74.4–94.9%) at 1 year and 63.7% (95% CI, 45.7–79.9%) at 2 years. Nodal and distant recurrence rates were 17.8% (95% CI, 7.5–31.2%) and 26.9% (95% CI, 7.4–53.0%), respectively. The rates of grade 1, grade 2, and grade 3 toxicity (CTCAE) were 12.6% (95% CI, 6.7–19.9%), 6.7% (95% CI, 3.3–11.2%), and 1.4% (95% CI, 0.0–5.3%), respectively. No grade 4 or 5 events were observed across the studies. Conclusion: SABR for inoperable early-stage, node-negative SCLC is locally effective with limited toxicity. Prospective studies are required to further evaluate the role of SABR for patients at higher risk of toxicity with surgery or combined chemoradiation.